2015
DOI: 10.1515/cdbme-2015-0083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short-term fixation with mixed formalin or ethanol solution on the mechanical properties of human cortical bone

Abstract: Bone specimens obtained for biomechanical experiments are fresh-frozen for storage to slow down tissue degradation and autolysis in long-term storage. Alternatively, due to infectious risks related to the fresh tissues, xative agents are commonly used. However, xatives will likely change the mechanical properties of bone. Existing studies on this issue gave controversial results that are hardly comparable due to a variety of measurement approaches. For this reason, the in uence of ethanol and a formalin-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The fixation method we used potentially limits transferability of the data [ 40 , 41 ]. Although Linde and Sorensen did not find relevant changes in the biomechanical behaviour of human trabecular bone specimens stored in 70% methanol for 100 days [ 42 ] and Mick et al stated no differences for ultimate bending of human cortical specimens after rehydration due to formalin or ethanol-fixation (96%) compared to fresh frozen bones [ 43 ], we do not know the relevance of possible modifications caused by our treatment protocol. Anyway, as the comparison between the groups is more significant than the absolute values and all bones were treated equally, this systematic failure should not affect the main deductions drawn by our study.…”
Section: Discussionmentioning
confidence: 73%
“…The fixation method we used potentially limits transferability of the data [ 40 , 41 ]. Although Linde and Sorensen did not find relevant changes in the biomechanical behaviour of human trabecular bone specimens stored in 70% methanol for 100 days [ 42 ] and Mick et al stated no differences for ultimate bending of human cortical specimens after rehydration due to formalin or ethanol-fixation (96%) compared to fresh frozen bones [ 43 ], we do not know the relevance of possible modifications caused by our treatment protocol. Anyway, as the comparison between the groups is more significant than the absolute values and all bones were treated equally, this systematic failure should not affect the main deductions drawn by our study.…”
Section: Discussionmentioning
confidence: 73%
“…The storage period in 70% ethanol was less than a month. Short-term storage in 70% ethanol has been shown to have no negative effects on the mechanical properties [29,30]. Prior to mechanical testing, femurs were rehydrated in saline for 24 h at 4°C.…”
Section: Three-point Bendingmentioning
confidence: 99%
“…However, these postyield properties demonstrated significant interaction effects which necessitated separate analyses within each preservation group. Previous studies have indicated that the negative effects of soaking in ethanol can be reversed with rehydration prior to testing in compression [6], tension [7], and beam bending [8]. However, one of these three studies only reported preyield parameters [6], and the postyield properties reported in the other two were limited to ultimate stress [8] or ultimate stress and strain to failure [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the negative effects of soaking in ethanol can be reversed with rehydration prior to testing in compression [6], tension [7], and beam bending [8]. However, one of these three studies only reported preyield parameters [6], and the postyield properties reported in the other two were limited to ultimate stress [8] or ultimate stress and strain to failure [7]. Although the one study reporting strain to failure did not show a significant difference [7], the sample size was low which necessitated non-parametric statistical analyses and a loss of power as indicated by the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation